The stone circle ebook - Griffiths, Elly (Ruth Galloway Mystery, 2019)
In this delightfully creepy mystery, Ruth Galloway—whom #1 New York Times bestselling author Louise Penny calls "a captivating amateur sleuth"—is haunted by a ghost from her past, just as her future lands on shaky ground. ¶ "Its patented combination of mysterious circumstances, police procedure, and agonizing relationship problems will keep you reading, and feeling, all night." —Kirkus Reviews (starred review) ¶ Ruth's partner in crime, DCI Nelson, has been receiving threatening letters. They are anonymous, yet reminiscent of ones he has received in the past, from the person who drew him into a case that's haunted him for years. At the same time, Ruth receives a letter purporting to be from that very same person—her former mentor, and the reason she first started working with Nelson. But the author of those letters is dead. Or is he? The past is reaching out for Ruth and Nelson, and its grip is deadly.